2015
DOI: 10.1089/hum.2015.027
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis Gene Therapy in the UK and Elsewhere

Abstract: The cystic fibrosis transmembrane conductance regulator (CFTR) gene was identified in 1989. This opened the door for the development of cystic fibrosis (CF) gene therapy, which has been actively pursued for the last 20 years. Although 26 clinical trials involving approximately 450 patients have been carried out, the vast majority of these trials were short and included small numbers of patients; they were not designed to assess clinical benefit, but to establish safety and proof-of-concept for gene transfer us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 112 publications
0
68
0
Order By: Relevance
“…These treatments should be effective irrespective of CFTR mutation. After the discovery of the CFTR gene in 1989, numerous gene therapy clinical trials have been performed, with minimal direct clinical benefit established (42). However, rather than emphasizing clinical end points, these early studies were performed primarily to illustrate the clinical safety and proof of concept for gene therapy/editing techniques.…”
Section: Non-cftr-based Therapeutic Approachesmentioning
confidence: 99%
“…These treatments should be effective irrespective of CFTR mutation. After the discovery of the CFTR gene in 1989, numerous gene therapy clinical trials have been performed, with minimal direct clinical benefit established (42). However, rather than emphasizing clinical end points, these early studies were performed primarily to illustrate the clinical safety and proof of concept for gene therapy/editing techniques.…”
Section: Non-cftr-based Therapeutic Approachesmentioning
confidence: 99%
“…Concerning the airways, many studies have shown that PEI can promote gene transfer in vivo with an efficiency corresponding up to 5% of pulmonary cells, when administered intravenously [24]. This percentage of positively transfected cells seems to be in the lower range needed to obtain the therapeutic effect, at least for what is concerning cystic fibrosis gene therapy [25].…”
Section: Cationic Polymersmentioning
confidence: 99%
“…Academia and industry had assumed that the lung would be an easy, non-invasive target, overlooking the fact that potent extra-and intra-cellular barriers interfere with gene transfer into airway epithelial cells. 1 The realisation that CF gene therapy is not 'low-hanging fruit' caused interest to wane and many academics and industry to chase easier disease targets. After the turn of the century, CF gene therapy was pursued by only a small, but highly motivated, number of groups.…”
mentioning
confidence: 99%
“…[2][3][4] To date, approximately 27 CF gene therapy trials involving ~600 patients have been conducted. 1 All but two were single-dose phase I/IIa safety studies, which also included assessment of molecular endpoints (measurement of vector-specific mRNA and CFTR-mediated ion transport).…”
mentioning
confidence: 99%
See 1 more Smart Citation